MENDESAIN KEBIJAKAN PUBLIK: PENDEKATAN STRATEGIS DALAM MEWUJUDKAN PEMERINTAHAN YANG EFEKTIF DAN RESPONSIF - Sunni Chotijah Balqis; Thabita Clarista Rahmania Oktaf; Teza Putri Indahsari; Lutfiatul Masruroh; Ria Angin Angin (SS&H: Studies in Social Sciences and Humanities, 2025)
As a crucial component of efficient and inclusive government, this study attempts to offer a conceptual and practical knowledge of the public policy-making process. This paper examines the important phases of the policy design process, including problem identification, policy formulation, implementation, and evaluation, using a descriptive qualitative approach based on a literature review. The essay also addresses the significance of employing data and evidence-based analysis to create fair and effective policies, as well as the role of important players in the policymaking process. The findings demonstrate that the original design of public policy, which must be mature, participative, evidence-based, and contextualized to the sociopolitical circumstances of the community, considerably influences its success. Therefore, creating public policy is a strategic process that establishes a policy's legitimacy and efficacy rather than merely being an administrative one.